Restorative Masculine Integration Theory - Angelucci, Todd; Gallegos, Julian (American Journal of Men s Health, 2025)
The Restorative Masculine Integration Theory (RMIT) introduces a strengths-based, systems-oriented framework for promoting healthy masculinity through healing, leadership, and relational engagement. Developed in response to the adverse effects of masculine suppression, such as emotional disengagement, burnout, and polarity collapse, RMIT outlines a five-phase Cycle of Masculine Restoration: reclaimed masculinity, emotional safety and trust, grounded leadership, rebalanced gender polarity, and healing with cultural renewal. These stages are underpinned by core concepts including psychological safety, peer mentorship, emotional literacy, and authentic masculinity. Drawing from interdisciplinary foundations in gender studies, emotional intelligence, trauma-informed practice, polarity theory, and servant leadership, RMIT offers an adaptable framework for use across clinical, educational, organizational, and policy settings. Its alignment with the MANifest Health Theory further strengthens its applicability in men's health promotion. This manuscript elaborates the theory's conceptual development, visual model, and practical implications, while identifying future directions for empirical validation and inclusive application. RMIT advances a timely and restorative model for transforming masculine identity into a source of individual and collective resilience.
Keywords: Conceptual framework; Conceptual model; Culture theory; Empirical research; Gender identity; Grounded theory; Identity (music); Masculinity; PsycINFO; dept.nur; emotional literacy; masculinity; men’s health; peer mentorship; polarity; psychological safety; theory development; trauma-informed care

Virtual Faculty Development Program for Doctoral Advising - Penny, Frances (Nurse Educator, 2025)
Keywords: Academic advising; Career development; Faculty development; MEDLINE; Professional development; Virtual patient; dept.nur

Factors Contributing to Increased Mental Health Symptoms and Suicidality Among Sexual and Gender Minority Youth: A Scoping Review of Quantitative Research - Lopes, Daniela (Journal of Psychosocial Nursing and Mental Health Services, 2025)
Keywords: Anxiety; Clinical psychology; Depression (economics); Medicine; Mental health; Poison control; Psychiatry; Psychological intervention; Psychology; Psychosocial; Sexual minority; Sexual orientation; Suicidal ideation; Suicide prevention; dept.nur

Generational Differences in Nursing Students' Perceptions of Faculty Caring Behaviors and Presence in Online Registered Nurse to Bachelor of Science in Nursing Programs. - Macario, Kimberly Cardaci (International Journal for Human Caring, 2025)
Abstract: The purpose of this study was to explore how students of different generations perceived presence and caring behaviors by faculty in online Registered Nurse to Bachelor of Science in Nursing programs. Results showed that millennials reported statistically significant higher perceptions of social presence when compared with nonmillennials. Although generation was not a predictor of caring, all presence subscales were positively and significantly correlated with the total caring score. Teaching presence was a significant predictor of students' perceptions of caring in online courses.
Keywords: Adult; Adult: 19-44 years; Age Factors; Caring Evaluation; Colleges and Universities; Conceptual Framework; Convenience Sample; Correlational Studies; Descriptive Research; Descriptive Statistics; Education, Non-Traditional; Education, Nursing, Baccalaureate; Educational Measurement; Exploratory Research; Faculty, Nursing; Faculty-Student Relations; Human; Intergenerational Relations; Learning Environment; Middle Age; Middle Aged: 45-64 years; Nursing Practice, Evidence-Based; Presence; Professional-Patient Relations; Program Evaluation; Quantitative Studies; Questionnaires; Registered Nurses Psychosocial Factors; Regression; Social Behavior Evaluation; Statistical Significance; Student Attitudes Evaluation; Students, Nursing Psychosocial Factors; Summated Rating Scaling; Teaching Methods; United States; dept.nur

Summer Nursing Symposium: An Immersive Educational Program Inspiring Underrepresented Minorities for College and a Career in Nursing - Knickerbocker, Joshua; Krol, Maria; Bartlett, Andrew; Borgognone, Kristen; Martinez, Kelly (Hispanic Health Care International, 2025)
Keywords: Medical education; Medicine; Nurse education; Nursing; Psychology; Underrepresented Minority; dept.nur; peer-reviewed